The Effect of Organizational Performance, Competitive Advantage on the Financial Sector of Chemical Manufacturing Industry in Banten Province - Uli Wildan Nuryanto; Masyhudzulhak Djamil MZ; Achmad Hidayat Sutawidjaya; Ahmad Badawi Saluy (Yayasan Ilomata, 2020)
In the current dynamic business environment, the competition is getting stiffer and performance organizational becomes an issue, the characteristics that occurred in the industrial revolution 4.0. This condition requires organizations to increase their performance to be sustained. Competence and knowledge management as internal resources that refer to RBV are strengths that are very important as predictors in improving performance. For this reason, the study has explored the indicators of each of the predictors and also test the relationships between a latent variables that have been hypothesized. This research focuses on the industrial chemical manufactur in Banten Province Indonesia which is become the province with the third-largest number of chemical firms in Indonesia. Regarding the central bureau statistics of Indonesia, the values of productivity, and human resources capability from the downstream chemical manufacturing sector below the target. This research using the SEM-PLS method to measure 97 respondents from the level supervisor and managerial. The final results provide a positive and significant relationship between competence and knowledge management through competitive advantage and organizational performance. Competitive advantage also increases the relationship between competence and knowledge management through organizational performance. This result has implications for managerial levels to increase human resources performance so it can improve the firm competitive advantage.